Analisis Praktek Qardh bagi Petani Jagung di Nagari Salareh Aia Timur, Kecamatan Palembayan, Kabupaten Agam Perspektif Ekonomi Islam - Sindi Saputri; Endri Yenti (Lembaga Yasin AlSys, 2026)
This study was motivated by the practice of qardh among corn farmers, accompanied by provisions requiring borrowers to pledge their corn fields to the toke providing the loan, to sell their harvests to that toke, to face differences in purchase prices between indebted and non-indebted farmers, and to accept the toke’s taking of profit from the sale of corn harvests per ton. This study aims to identify the practice of qardh in Nagari Salareh Aia Timur and to analyze it from the perspective of Islamic Economics. This study employed a descriptive qualitative method, with data collected through observation, interviews, and documentation, while data processing and analysis were carried out in three stages, namely data collection, data reduction, and conclusion drawing. The results showed that the practice of qardh between corn farmers and toke in Nagari Salareh Aia Timur was generally influenced by economic factors and the farmers’ limited access to transportation to reach their corn fields. The practice constituted a form of lending that was not fully based on the spirit of mutual assistance, with the contract taking the form of an oral agreement covering the entire loan arrangement. From the perspective of Islamic Economics, the implementation of Islamic Economic principles in this practice has not been fully realized, because corn farmers have applied only some of the existing principles. These findings affirm that the practice of qardh among corn farmers in the area still requires adjustment in order to be more in line with the principles of Islamic Economics.